Six Weeks of Polarized Versus Moderate Intensity Distribution: A Pilot Intervention Study - Röhrken, Golo; Held, Steffen; Donath, Lars (Frontiers in Physiology, 2020)
Background: Previous research indicates that polarized training intensity distribution (TID) programmes could increase endurance performance. Short-distance triathletes, however, perform most of their competition-specific training centered around moderate-intensity intervals. There is still a lack of conclusive evidence as to which programme is more efficient in triathlete training. This pilot study examined six weeks of intervention using polarized intensity distribution compared to more moderate TID and the effects on sub-maximal and maximal performance parameters during the activities, running and cycling. Methods: Fifteen moderately trained triathletes were either assigned to an intervention group (INT, n = 7, 2 females / 5 males, Age: 29.1 ± 7.6) or a control group (CON, n = 8, 2 females / 6 males, Age: 30.3 ± 6.1). To allocate the groups, we used the minimization method (Strata: gender, age, competition times, training volume per week). In order to assess performance indices, the participants underwent tests in incremental cycling and running before and after the intervention period until objective exhaustion level. CON employed a moderate TID with either medium-intensity (MIT) or low-intensity training (LIT). INT used polarized training intensity distribution (TID), with either LIT or high-intensity training (HIT). Average training hours and anthropometric data did not indicate any differences between CON and INT during the study period. We applied the polarization index of > 2 in INT (2.1 ± 0.4) and < 1 in CON (0.9 ± 0.3). Results: Both groups notably improved their lactate threshold 2 (+ 2.8 ± 5.1 %, p = 0.026) and peak (+ 5.4 ± 6.2 %, p = 0.002) running performance. We did not observe statistically significant time x group interaction effects in any of the performance outcomes between both groups. Conclusion: Polarized TID in moderately trained triathletes did not prove to be superior compared to a more moderate TID.